Tunable high power fiber laser using an AWG as the tuning element - Abdul Latif, Amirah; Ahmad, Harith; Awang, Noor Azura; Zulkifli, Mohd Zamani; Pua, C. H.; Ghanib, Zawajer A; Harun, Sulaiman Wadi (Pleiades Publishing, Ltd, 2011)
In this paper, a design of a High Power Tunable Fiber Laser (HPTFL) in Cband region from 1536.7 to 1548.6 nm is set forth with Erbium Doped Fibers (EDFs) being used as a seeding signal and a booster amplifier. With a 1 × 16 channels Arrayed Waveguide Grating (AWG), this setup is capable of gener ating 16 different wavelengths with an average output power of 20.7 dBm.